2023
DOI: 10.1039/d2cc06549e
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate-dependent phase switching in the square lattice topology coordination network [Ni(4,4′-bipyridine)2(NCS)2]n

Abstract: Switching coordination networks (CNs) featuring stepped sorption isotherms that are accompanied by phase changes offer promise for gas storage and separation applications. However, their responsiveness to different adsorbates remains largely...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…This can be ascribed to the permanent dipole moment of C 3 H 4 and its large van der Waals size, which enables highly exothermic adsorption relative to CO 2 , as we have reported in switching sql topology networks. 44,45 X-ddi-1-Ni-β displayed a single-step type F-IV isotherm 8 with gateopening at 0.50 bar and uptake of 3.32 mol•mol −1 at 1 bar. Xddi-2-Ni-β exhibited a two-step type F-IV 2 (F-IV m ) isotherm under the same conditions: the first step occurred at 0.13 bar with an uptake of 2.00 mol•mol −1 after opening, while the second step appeared at 0.65 bar with an uptake of 6.34 mol• mol −1 at 1 bar.…”
Section: Synthesis Of the X-ddi Platform And Structuralmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be ascribed to the permanent dipole moment of C 3 H 4 and its large van der Waals size, which enables highly exothermic adsorption relative to CO 2 , as we have reported in switching sql topology networks. 44,45 X-ddi-1-Ni-β displayed a single-step type F-IV isotherm 8 with gateopening at 0.50 bar and uptake of 3.32 mol•mol −1 at 1 bar. Xddi-2-Ni-β exhibited a two-step type F-IV 2 (F-IV m ) isotherm under the same conditions: the first step occurred at 0.13 bar with an uptake of 2.00 mol•mol −1 after opening, while the second step appeared at 0.65 bar with an uptake of 6.34 mol• mol −1 at 1 bar.…”
Section: Synthesis Of the X-ddi Platform And Structuralmentioning
confidence: 99%
“…Therefore, preserving this connectivity while altering the organic linker allows for construction of platforms of structurally related or, ideally, isostructural materials. In this context, switching MOF platforms comprised of four-connected (4-c) nodes were extensively studied through a series of 2D nets with square-lattice ( sql ) topology , and 3D nets with diamondoid ( dia ) topology , (see Tables S1 and S2). Additionally, six-connected (6-c) nodes, usually resulting in 3D primitive cubic ( pcu ) frameworks, have been explored in depth. , Rod building block (RBB)-based MOFs ,, are also known to exhibit breathing (e.g., MIL-53) and show switching behavior (e.g., M­(bdp)).…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Recently, we reported that the previously known square lattice (sql) CN, 33,34 [Co(bpy) 2 (NCS) 2 ] n (bpy = 4,4′-bipyridine), sql-1-Co-NCS, exhibits recyclable switching between its "closed" nonporous and "open" porous phases induced by CO 2 or C 8 aromatics. 35,36 We coined the term "switching adsorbent layered materials" (SALMAs) for such sorbents and they hold promise for gas storage and hydrocarbon separations, [36][37][38][39][40][41][42] prompting us to explore the feasibility of their large-scale manufacture. In our previous work, 35 we prepared sql-1-Co-NCS by applying heat under vacuum to its guest-loaded variant sql-1-Co-NCS•2TFT (TFT = α,α,α-trifluorotoluene), which was synthesized by self-assembly of Co(NCS) 2 and bpy using the SD method in the presence of organic solvents (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) have gradually become one of the most promising porous materials [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] owing to their excellent designability and long-range ordered porous structures. [20][21][22][23][24][25][26][27][28][29] Among numerous synthesis strategies, postsynthetic modification of known MOF structures to achieve specific functions breaks the barrier of introducing functional sites through direct synthesis.…”
Section: Introductionmentioning
confidence: 99%